PARTICIPATION OF AN ADVOCATE AS A REPRESENTATIVE IN CIVIL PROCEEDINGS: RIGHTS AND OBLIGATIONS (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ABSTRACT This thesis explores the role of advocates as representatives in civil proceedings, emphasizing their rights and obligations. It highlights how advocates influence the judicial process by ensuring fair representation of litigants' interests. Key duties, such as loyalty, confidentiality, and competence, are discussed alongside rights like accessing case files and presenting evidence. The balance between effective client representation and adherence to legal and ethical standards is examined, as well as challenges like conflicts of interest. This analysis aims to deepen understanding of advocates' roles and contribute to improving civil justice.